2006
DOI: 10.1021/om060912v
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Stereoelectronic Effects in Complexes of Phospholanes, Phosphinanes, and Phosphepanes and Their Implications for Hydroformylation Catalysis

Abstract: derived from L b 7 shows negligible hydroformylation activity but rapid octene isomerization activity. The overall conclusion is that, with the rhodium complexes of the simple phosphacycles described here, no special effect of the rings was observed in the hydroformylation catalysis. An R-substituent effect is identified as a common feature in several high-activity hydroformylation catalysts derived from phosphinanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 39 publications
0
63
0
Order By: Relevance
“…The structure ( Figure 4) has the expected octahedral arrangement of ligands with phenop trans to a single carbonyl and the remaining CO donors coplanar. The W-P bond length of 2.6292(10) Å is long for this type of complex when compared to related structurally characterised derivatives such as [W(CO) 5 (PMe 3 )] [2.516(2) Å], [15] [W(CO) 5 [17] but is shorter than the value of 2.686 Å observed in the tri-tertbutylphosphane analogue. [18] As expected the W-C bond length to the carbonyl carbon trans to the phosphane is the shortest at 1.985(5) Å compared to the other W-C bond lengths which are all longer than 2.040 Å.…”
Section: Syntheses and Structure Of The Metal Complexes Of Phenopmentioning
confidence: 89%
See 2 more Smart Citations
“…The structure ( Figure 4) has the expected octahedral arrangement of ligands with phenop trans to a single carbonyl and the remaining CO donors coplanar. The W-P bond length of 2.6292(10) Å is long for this type of complex when compared to related structurally characterised derivatives such as [W(CO) 5 (PMe 3 )] [2.516(2) Å], [15] [W(CO) 5 [17] but is shorter than the value of 2.686 Å observed in the tri-tertbutylphosphane analogue. [18] As expected the W-C bond length to the carbonyl carbon trans to the phosphane is the shortest at 1.985(5) Å compared to the other W-C bond lengths which are all longer than 2.040 Å.…”
Section: Syntheses and Structure Of The Metal Complexes Of Phenopmentioning
confidence: 89%
“…Yellow [W(CO) 5 (κ 1 -phenop)] (4) was isolated in good yield from the 1:1 reaction of [W(CO) 5 (THF)] and phenop in THF. The isolated complex is freely soluble in most common organic solvents, and is air-stable in the solid state.…”
Section: Syntheses and Structure Of The Metal Complexes Of Phenopmentioning
confidence: 99%
See 1 more Smart Citation
“…Prigle et al reported the synthesis of the platinum complexes of several 5-, 6-and 7-membered P-heterocycles [33,34]. Gouygou et al synthesized a few bisphosphole platinum-complexes [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, bimetallic catalysis has attracted considerable interest in recent years [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%